China's Role in Burma's Development. (15th July 2014) - Renwick, Neil
Abstract China has been a long‐standing partner for Burma (Myanmar), providing important political, military and economic support. Burma's reform process poses new questions and challenges for China. China's interests in Burma are primarily economic‐driven by its need for strategic resources and are highly controversial. This study argues that China's approach to Burma's development is determined by its own national economic interests. Beijing's view is that this is a 'win‐win' situation. This is a view under critical review in Burma as it seeks to re‐balance its foreign relationships. This article details the critical point at which Sino–Burmese relations now stand, explains Burma's current development profile, outlines Chinese involvement in Burma and explains China's development approach to Burma in terms of China's national economic, political and security interests.